COVID-19 and Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers: What Is the Evidence? - Patel, Ankit B; Verma, Ashish (JAMA : the journal of the American Medical Association, 2020)
This Viewpoint reviews the pathophysiological and observational basis for speculating that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) might worsen clinical outcomes for patients with COVID-19, and summarizes guidance from specialty societies to continue the drugs in patients who need them pending more definitive evidence of harm.